Comparison between Echinococcus granulosus sensu stricto (G1) and E. canadensis (G6) mitochondrial genes (cox1 and nad1) and their related protein models using experimental and bioinformatics analysis. (April 2019) - Sadjjadi, Seyed Mahmoud; Ebrahimipour, Mohammad; Sadjjadi, Fatemeh Sadat
Graphical abstract: Highlights: Cystic echinococcosis is parasitic disease, caused by different strains of Echinococcus granulosus with different hosts and pathogenicity. The affinity of E. granulosus sensu stricto and E. canadensis for localizing the organs seems to be different with unknown cause. Experimental and bioinformatics analysis was used to find out cox1 and nad1 genes and their protein models in E. granulosus and E. canadensis . Cystic echinococcosis cysts of E. granulosus s.s. and E. canadensis of differences are reflected in two important proteins: COX1 and NAD1. The differences in the 3D structure of proteins may be used for interpreting the pathogenicity and localization affinity of two species. Abstract: Background: Cystic echinococcosis (CE) as a zoonotic parasitic disease, remains a health challenge in many parts of the world. There are different species of Echinococcus granulosus sensu lato with different pathogenicity and host preferences.Different procedures have been applied for characterization of Echinococcus taxa in which two mitochondrial genes, cox1 and nad1 have been used more common. They have been able to differentiate E. granulosus sensu stricto and E. canadensis species in different hosts. The affinity of E. granulosus sensu stricto and E. canadensis species for localizing different organs seems to be different. To what such affinity and related pathogenicity could be related, is not known, so far. Bioinformatics analysis may be helpful to interpret such difference by investigating the genes and their related protein models between different species infecting human and animals. The current work was designed to study the differences between E. granulosus s.s. and E. canadensis species mitochondrial genes (cox1 and nad1) and related protein models of CE cysts by experimental and bioinformatics analysis. Materials and methods: Different human and animal CE cysts were collected and their DNA was extracted and sequenced based on their cox1 and nad1 genes. In order to determine the E. granulosus s.s. and E. canadensis species of the samples, BLAST analysis was performed on sequenced genes. Three sequences were selected for analysis and were deposited in GenBank. Moreover, the sequence number of KT988116.1 which belonged to E. canadensis from our already deposited in GenBank was also selected. Alignment and phylogenetic analysis were performed on the sequences using BioEdit and MEGA7 software. The raw sequences of translated proteins belonged to the mentioned genes were obtained from Protein database in NCBI. The secondary structure was determined by PSIPRED Protein Sequence Analysis Workbench. The tertiary models of COX1 and NAD1 proteins in both genotypes were constructed using Modeler 9.12 software and their physicochemical features were computed using ProtParam tool in ExPASY server. Results: BLAST analysis on sequenced genes showed that the samples belonged to E. granulosus s.s. and E. canadensis species. These sequences were deposited in GenBank with accession numbers: JN579173.1, KF437811.1, and KY924632.1. The results showed that proteins of COX1 of E. granulosus s.s., COX1of E. canadensis, NAD1of E. granulosus s.s. and NAD1of E. canadensis species, consisted of 135, 122, 120 and 124 amino acids, respectively. The aligned sequences of translated proteins belonged to COX1 and NAD1 enzymes in E. granulosus s.s. and E. canadensis species were different; such that alignment COX1 sequence between E. granulosus s.s. and E. canadensis species showed that amino acids were different in 6 positions. This difference for NAD1 sequences were different in 19 positions. The secondary structure determined by PSIPRED showed differences in coil, strand and helix chains in COX1 and NAD1 proteins in E. granulosus s.s. and E. canadensis species. Comparison between three-dimensional structures (3D) of COX1 protein model in E. granulosus s.s. and E. canadensis species demonstrated an additional helix with two conserved iron binding sites in the COX1 protein of E. granulosus s.s. species. Conclusion: E. granulosus s.s. and E. canadensis species differences are reflected in two important proteins: COX1 and NAD1. These differences are demonstrable in the 3D structure of proteins of both strains. So, the present study is adding to our understanding of the difference in molecular sequences between the E. granulosus s.s. (G1) and E. canadensis (G6) which may be used for interpreting the difference between the pathogenicity and localization affinity in these two important helminthic zoonosis.